2021
DOI: 10.1016/j.envres.2020.110294
|View full text |Cite
|
Sign up to set email alerts
|

Prospect of biobased antiviral face mask to limit the coronavirus outbreak

Abstract: The rapid spread of COVID-19 has led to nationwide lockdowns in many countries. The COVID-19 pandemic has played serious havoc on economic activities throughout the world. Researchers are immensely curious about how to give the best protection to people before a vaccine becomes available. The coronavirus spreads principally through saliva droplets. Thus, it would be a great opportunity if the virus spread could be controlled at an early stage. The face mask can limit virus spread from both inside and outside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 18 publications
0
92
0
Order By: Relevance
“… 52 55 Some studies have confirmed the airborne transmission of COVID-19 through saliva droplets, 35 , 56 whereas others have established dynamic flow models of airborne particles containing SARS-CoV-2 trying to elucidate the contexts in which COVID-19 airborne transmission mainly occurs. 57 , 58 Two factors are considered in evaluating the airborne transmission: (i) the viral load in saliva and mucosae droplets, and (ii) the survival rate of the SARS-CoV-2 in the environment. It has been proven that the viral load can vary depending on the specimen being considered.…”
Section: Airborne Transmission Of Sars-cov-2mentioning
confidence: 99%
“… 52 55 Some studies have confirmed the airborne transmission of COVID-19 through saliva droplets, 35 , 56 whereas others have established dynamic flow models of airborne particles containing SARS-CoV-2 trying to elucidate the contexts in which COVID-19 airborne transmission mainly occurs. 57 , 58 Two factors are considered in evaluating the airborne transmission: (i) the viral load in saliva and mucosae droplets, and (ii) the survival rate of the SARS-CoV-2 in the environment. It has been proven that the viral load can vary depending on the specimen being considered.…”
Section: Airborne Transmission Of Sars-cov-2mentioning
confidence: 99%
“…The fiber diameter of each nonwoven fabric was observed by SEM ( Figure S2 and Table S7 ). However, most of the airborne viruses (Corona) spread through the aerosol are in nanometers [ 48 , 49 , 50 , 51 ]. The fiber diameter of the nanofiber prepared in this study was 375 + 69 nm, and the filter efficiency was improved by reducing the fiber diameter.…”
Section: Resultsmentioning
confidence: 99%
“…In another safer approach, the extracts of licorice roots as bio‐based antiviral agents were embedded into the mask structure, [ 93 ] while the extracts already demonstrated powerful antiviral activities against various viruses including RSV, HIV, and SARS‐CoV. [ 147 , 148 ] Practically, electrospinning of an aqueous solution of polyvinyl alcohol (PVA) containing licorice roots extracts was used to prepare nanofibrous membrane as the active layers of the mask ( Figure 14 a ).…”
Section: Modification Of Masksmentioning
confidence: 99%